Decreasing in pressure interval of near-miscible flooding by adding intermediate hydrocarbon components. Issue 3 (4th May 2018) - Chen, Hao; Tang, He; Zhang, Xiansong; Li, Bowen; Li, Baozhen; Shen, Xiong
Abstract: Oil quality and gas sources are two main limitations for the promotion of CO2 miscible flooding in China. However, near-miscible flooding was proposed recently which can obtain comparable recovery based on both experiments and field tests. The discovery of gas reservoir, which contains high content (24–90 mol%) of CO2 in QHD offshore oilfield, provides big potential for the implementation of CO2 flooding in China. In this paper, based on the slim tube test and slim tube simulation with denser test points, specific regions of near-miscible flooding for different CO2 contents were determined by the relation curves of displacement efficiency, IFT, and pressure. For the targeted well QHD 29-2E-5, the lower limit of CO2 content for achieving near-miscible flooding is 64%. To enlarge the scope and potential of near-miscible flooding, the feasibility of adding intermediate components (C2 –C6 ) in the injection gas to decrease the pressure interval of near-miscible flooding was investigated. Results showed that for each 10% decrease in CO2 content, 2.5% of the intermediate components (C2 –C6 ) of the production gas are needed to add for achieving near-miscible flooding in the well QHD 29-2E-5.